IMPROVING THE STUDENTS’ SPEAKING ABILITY THROUGH ORAL PRESENTATION - Andita Febriansari Dana Putri; Sudarsono Sudarsono; Syarif Husin (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2019)
AbstractThis research was done to investigate how oral presentation technique improves students’ speaking ability. This classroom action research was conducted in 2 cycles of which each consists of four stages of planning, acting, observing and reflecting. The subject of this research was Year-11 students of SMAN 6 Pontianak in Academic Year 2018/2019. There were 33 students of MIPA 4 who participated in this research. The data were gathered from the students’ performance test, observation checklist, and field notes. Based on the data, the students showed improvement in their speaking ability. It was shown by the students’ enthusiasm to pay attention and follow every activity during the teaching and learning process. The implementation of this technique encouraged the students to speak and share their ideas in front of people. The data collected from the students’ performance test also revealed the improvement from cycle to cycle. In conclusion, the implementation of oral presentation technique improved students’ speaking ability.Keywords: Improving, Speaking Ability, Oral Presentation